2011
DOI: 10.3892/ol.2011.439
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and treatment comparison in early-stage small cell carcinoma of the uterine cervix

Abstract: Abstract. Small cell carcinoma of the uterine cervix (SCCUC) is rare and its biologic behavior is aggressive. To analyze prognostic factors and determine optimal therapy in patients with International Federation of Gynecology and Obstetrics (FIGO) stage IB1-IIA SCCUC, we retrospectively reviewed 96 patients (14 patients treated in our center and 82 patients identified by a search on PubMed) treated with radical surgery (SU), surgery plus adjuvant chemotherapy (SU+Chemo), or surgery plus adjuvant chemotherapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 30 publications
3
17
2
5
Order By: Relevance
“…As shown in previous studies, deep stromal invasion tended to be associated with poor survival. 7,13,19,20 In our study, deep stromal invasion was also a prognostic factor in patients with early-stage disease. Patients with deep stromal invasion had a 2.9 times higher risk of cancer death (P = 0.011).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As shown in previous studies, deep stromal invasion tended to be associated with poor survival. 7,13,19,20 In our study, deep stromal invasion was also a prognostic factor in patients with early-stage disease. Patients with deep stromal invasion had a 2.9 times higher risk of cancer death (P = 0.011).…”
Section: Discussionsupporting
confidence: 59%
“…The more advanced stage is correlated with a higher risk of poorer survival. 1,3,5,7,12,13,18,19 Although FIGO stage has been identified as a strong prognostic factor, all reference groups used in previous studies were either FIGO stage I or stage I to IIA (early stage) to compare the effects of FIGO stage on survival in multivariable analysis. 3,5,7,12 The Surveillance, Epidemiology, and End Results (SEER) study showed that compared with stage I, patients with SNEC with stage IV had a 4.6 times higher risk of death (P G 0.001) and patients with stage III had a higher risk 2.4 times (P = 0.017).…”
Section: Discussionmentioning
confidence: 99%
“…25 However, in a report from Tian et al 26 of 96 women with stage IB1-IIA SCCC adjuvant chemotherapy after radical hysterectomy did not appear to improve the prognosis. Similar findings were reported by Cohen et al; postoperative adjuvant chemotherapy on 135 patients with stage I to stage IIA disease in an analysis of 188 cases of stage I to stage IV disease did not seem to influence outcome.…”
Section: Initial Treatmentmentioning
confidence: 94%
“…Reviews of the literature showed a similar local control rate for radical surgery (25%Y33%) and primary RT (6%Y25%, Table 3). 8,13,16,18,19 Surgery has the benefit of pathology information that is useful for tailoring adjuvant therapy. 20,21 On the other hand, RT has the benefit of reduced break time from chemotherapy.…”
Section: Discussionmentioning
confidence: 99%